2016
DOI: 10.1371/journal.pntd.0004934
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Leprosy and Those at Risk of Developing Leprosy by Detection of Antibodies against LID-1 and LID-NDO

Abstract: Leprosy is caused by Mycobacterium leprae infection and remains a major public health problem in many areas of the world. Challenges to its timely diagnosis result in delay in treatment, which is usually associated with severe disability. Although phenolic glycolipid (PGL)-I has been reported as auxiliary diagnostic tool, currently there is no serological assay routinely used in leprosy diagnosis. The aim of this study was to evaluate the effectiveness of two related reagents, LID-1 and LID-NDO, for the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
2
25
1
4
Order By: Relevance
“…Previous studies have suggested that the true prevalence of leprosy is underestimated because of diagnostic limitations inherent to large-scale control programs aimed at eventual disease elimination ( Amorim et al 2016 , WHO 2016 ). Thus, we evaluated the potential of a Mce1A-dependent antibody response against M. leprae as an alternative method for diagnosing leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the true prevalence of leprosy is underestimated because of diagnostic limitations inherent to large-scale control programs aimed at eventual disease elimination ( Amorim et al 2016 , WHO 2016 ). Thus, we evaluated the potential of a Mce1A-dependent antibody response against M. leprae as an alternative method for diagnosing leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of leprosy is based on clinical examination, bacilloscopy of the dermal lymph, and histopathology of skin lesion biopsies ( WHO 2016 ). Although bacilloscopy and histopathology are highly specific, these techniques show low sensitivity ( Amorim et al 2016 ). Moreover, negative results do not exclude the diagnosis of leprosy ( MS 2002 ).…”
mentioning
confidence: 99%
“…O estudo da hanseníase em uma perspectiva além do indivíduo acometido deve considerar o reconhecimento de possíveis RCD como elemento importante para melhor compreensão da dinâmica de transmissão e da adoção de ações oportunas de vigilância e controle. Ressalta-se, portanto, a necessidade de ampliar o foco das ações para os casos entre os contatos fora do domicílio, em especial nas áreas de maior endemicidade 3,18,19,20 . No entanto, os dados deste estudo sugerem que a experiência do adoecimento entre pessoas de uma mesma RCD parece não ser suficiente para desdobrar em ações de atenção e cuidado longitudinal, na perspectiva da integralidade do cuidado e da redução da carga da doença 21 .…”
Section: Tabelaunclassified
“…From the distribution of the endemicity rate of new leprosy cases registered in 2016, it was verified that 29.2% of Sobral's neighborhoods have a hyperendemic profile for leprosy, which makes the resident population with the potential to develop M. leprae, and reinforces the need for the development of strategic actions of active search, combat and control, since the number of cases registered in passive search may be greater when performing active search actions27 .Brazil has a heterogenic spatial distribution of cases of leprosy, guided by the economic social level. Southern states with greater socioeconomic development do not reach high levels or hyperendemicity of leprosy.…”
mentioning
confidence: 94%